Numerical Protection Analysis of Shen Xiu Intangible Cultural Heritage Based on Software Definition Technology - Zhu, Changyong; Lyu, Guan (International Journal of Communication Networks and Information Security (IJCNIS), 2023)
The role of numerical protection analysis in the digital protection of Shen Xiu’s intangible culture has changed the numerical value of Shen Xiu’s intangible culture and made the digital protection of Shen Xiu’s intangible culture a hot spot. However, in the process of numerical protection of intangible culture in Shen Xiu, there are some problems, such as poor digital collection effect and small amount of digital processing data. The main reason is that the traditional way of oral transmission and heart-to-heart transmission limits the development of digital numerical protection of intangible culture in Shen Xiu. Therefore, this paper proposes a digital protection method for Shen Xiu’s intangible culture based on software-defined technology and plans the characteristics of Shen Xiu’s intangible culture with different values. First of all, the data of Shen Xiu intangible culture in Shen Xiu are collected by software-defined technology, and the data of different values are summarized by software-defined technology, and the numerical division of Shen Xiu intangible culture is carried out according to the characteristics of Suzhou embroidery, leaving common characteristics. Then, according to the software-defined technology, the protective communication of numerical protection is carried out to promote the integration of the characteristics of Shen Xiu’s intangible culture. The results of numerical protection analysis show that software-defined technology can improve the numerical extraction level of Shen Xiu intangible culture, promote the development of digital numerical protection of Shen Xiu intangible culture by using software-defined technology, and meet the requirements of numerical protection of Shen Xiu intangible culture.